2020
DOI: 10.1111/jdv.16274
|View full text |Cite
|
Sign up to set email alerts
|

The National Psoriasis Foundation psoriasis treatment targets in real‐world patients: prevalence and association with patient‐reported outcomes in the Corrona Psoriasis Registry

Abstract: Introduction The National Psoriasis Foundation (NPF) published treat‐to‐target guidelines for psoriasis, yet their applicability in clinical practice remains unknown. Objectives To estimate the proportion of psoriasis patients meeting the NPF's body surface area (BSA) ‘target’ (≤1%) and ‘acceptable’ (≤3%) response criteria and the cross‐sectional associations of these criteria with patient‐reported outcomes (PROs) in the Corrona Psoriasis Registry. Methods Separately for three independent cross‐sectional cohor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 34 publications
1
5
0
1
Order By: Relevance
“…Although NAMCS data cannot directly estimate psoriasis prevalence, these surveys, conducted across 10 years, provide updated statistics of comorbid conditions across severity subgroups among all patients with psoriasis. The distribution of demographic factors and BMI among our patients with psoriasis were compatible with the recent National Psoriasis Foundation report [11], suggesting the representativeness of our estimates. According to NHANES (2003-6), the average BMI was 30.3 kg/m 2 in patients with psoriasis and 28.1 kg/m 2 in patients without psoriasis [17], which were close to our estimates.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Although NAMCS data cannot directly estimate psoriasis prevalence, these surveys, conducted across 10 years, provide updated statistics of comorbid conditions across severity subgroups among all patients with psoriasis. The distribution of demographic factors and BMI among our patients with psoriasis were compatible with the recent National Psoriasis Foundation report [11], suggesting the representativeness of our estimates. According to NHANES (2003-6), the average BMI was 30.3 kg/m 2 in patients with psoriasis and 28.1 kg/m 2 in patients without psoriasis [17], which were close to our estimates.…”
Section: Discussionsupporting
confidence: 88%
“…The US prevalence of psoriasis has increased [8]; 2009-10 estimates put the prevalence among adults at about 3.2% [9,10]. Among patients with psoriasis, about a quarter were severe cases, defined as > 10% body surface area involvement [11], and 10-15% were treated with biologics [12,13]. In a claims-based study, the most prevalent cardiometabolic comorbidities among patients with psoriasis were hyperlipidemia, hypertension, diabetes mellitus, and obesity [12].…”
Section: Introductionmentioning
confidence: 99%
“…Current guidelines and recommendations for IMIDs also recommend a treat-to-target approach [69,[82][83][84]. The value of such an approach is better patient outcomes in both the short and long term, which in addition to remission includes reductions in comorbidities and cardiovascular risk, as well as improvements in quality of life and productivity [81,[85][86][87][88][89][90]. However, several studies have shown that the practices outlined in guidelines do not translate well into the clinic with low rates of adherence to recommendations [70,[91][92][93][94].…”
Section: Achievement and Maintenance Of Remissionmentioning
confidence: 99%
“…Overall, 23.2% of patients after 6 months and 26.7% after 12 months of treatment achieved the more stringent currently leading criteria of PASI 90 (18.0 and 30.1% are reported in our study). However, the Corrona registry reports 43 and 64% of their patients achieving a much more stringent therapy target (BSA ≤1%) or the acceptable target (BSA ≤3%), respectively, at the 6-month visit, as well as an increase of these values up to 46 and 69% at the 12-month visit [30]. So, there is still a lot to be done until all treated patients reach the target.…”
Section: Discussionmentioning
confidence: 99%